Christopher Brumfit Award 2014. (8th September 2015) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> The Editor and Board of Language Teaching are pleased to announce that the winner of the 2014 Christopher Brumfit thesis award is Dr Hilde van Zeeland. The thesis was selected by an external panel of judges based on its significance to the field of second language acquisition, second or foreign language learning and teaching, originality and creativity and quality of presentation.